2017
DOI: 10.1038/srep40879
|View full text |Cite
|
Sign up to set email alerts
|

Panmixia and dispersal from the Mediterranean Basin to Macaronesian Islands of a macrolichen species

Abstract: The Mediterranean region, comprising the Mediterranean Basin and the Macaronesian Islands, represents a center of diversification for many organisms. The genetic structure and connectivity of mainland and island microbial populations has been poorly explored, in particular in the case of symbiotic fungi. Here we investigated genetic diversity and spatial structure of the obligate outcrossing lichen-forming fungus Parmelina carporrhizans in the Mediterranean region. Using eight microsatellite and mating-type ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 68 publications
(85 reference statements)
4
41
0
Order By: Relevance
“…Population genetic patterns in another lichenized fungus, Xanthoria parietina , based on RAPD-PCR markers, contrast starkly with the findings for L. pulmonaria; in the former, high genetic diversity and very few clones were found within small areas, even among adjacent individuals (Itten and Honneger 2010). The pattern recovered in X. parietina is similar to a study of Parmelina carporrhizans based on microsatellite loci, where high rates of migration were recovered among populations, except for isolated island populations (Alors et al 2017). A microsatellite-based study on Parmotrema tinctorum and its algal symbiont found that most dispersal was clonal over short distances, similar to L. pulmonaria , but still found evidence for high rates of sexual reproduction in the fungus (Mansournia et al 2012).…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…Population genetic patterns in another lichenized fungus, Xanthoria parietina , based on RAPD-PCR markers, contrast starkly with the findings for L. pulmonaria; in the former, high genetic diversity and very few clones were found within small areas, even among adjacent individuals (Itten and Honneger 2010). The pattern recovered in X. parietina is similar to a study of Parmelina carporrhizans based on microsatellite loci, where high rates of migration were recovered among populations, except for isolated island populations (Alors et al 2017). A microsatellite-based study on Parmotrema tinctorum and its algal symbiont found that most dispersal was clonal over short distances, similar to L. pulmonaria , but still found evidence for high rates of sexual reproduction in the fungus (Mansournia et al 2012).…”
Section: Introductionsupporting
confidence: 82%
“…The population genetic structure of X. parietina based on RAPD-PCR fingerprinting revealed high rates of genotypic diversity within populations, even on a microsites scale, and much lower genetic diversity between populations than within them (Itten and Honegger 2010). A study of the lichen Parmelina carporrhizans found a similar pattern of very high gene flow among most populations sampled, though it is a heterothallic species (Alors et al 2017). The pattern observed in these two species starkly contrasts with that of Lobaria pulmonaria , a heterothallic species that is often observed without sexual reproductive structures, in which apothecia usually are not produced until individuals are 15-25 years old (Denison 2003; Høistad and Gjerde 2011; Singh et al 2012).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Long‐distance dispersal of ascospores at various scales has been hypothesized in various studies of lichenized ascomycetes (Printzen et al ., ; Muñoz et al ., ; Geml et al ., ; de Paz et al ., ; Leavitt et al ., ; Bendiksby et al ., ), and the importance of ascospores for the colonization of new substrates has also been emphasized in non‐lichenized ascomycetes (Johannesson et al ., ; Fraaije et al ., ) and ectomycorrhizal fungi (reviewed in Douhan et al ., ). Ascospores disperse over long distances by wind (Gjerde et al ., ; Alors et al ., ) as they are of microscopic size and actively discharged. Rieux et al .…”
Section: Discussionmentioning
confidence: 99%
“…Long-distance dispersal of ascospores at various scales has been hypothesized in various studies of lichenized ascomycetes (Printzen et al, 2003;Muñoz et al, 2004;Geml et al, 2012;de Paz et al, 2012;Leavitt et al, 2013;Bendiksby et al, 2014), and the importance of ascospores for the colonization of new substrates has also been emphasized in nonlichenized ascomycetes (Johannesson et al, 2001;Fraaije et al, 2005) and ectomycorrhizal fungi (reviewed in Douhan et al, 2011). Ascospores disperse over long distances by wind (Gjerde et al, 2015;Alors et al, 2017) as they are of microscopic size and actively discharged. Rieux et al (2014) inferred the effective dispersal distances of ascospores (size 11.5-16.5 9 2.5-5.0 lm 2 ; www.cabi.org/isc/datasheet/35278) and conidia (size 30-132 9 2.5-5 lm 2 ) of a plant pathogen using spore trap plants.…”
Section: Discussionmentioning
confidence: 99%